Inventory Application Program on CV X in Semarang - Sayudin Sayudin (Politeknik Siber Cerdika Internasional, 2021)
This research uses qualitative approach. Qualitative approach is a process of research and understanding based on a methodology that investigates a phenomenal.Â According to jane richie qualitative research is an effort to improve the social world and its perspective in the world, in terms of concepts, behaviors, perceptions and problems about human beings are meticulous. From the discussion and observation of research, it can be concluded the following: First, it takes a long time to modulate the inventory of goods, therefore it is necessary to improve through development methods such as HIPO and basic visual coding. Second, The lack of thoroughness in modulates every item entering and exiting, for that the need for a program of application of inventory.